A Systematic Review of Emoji: Current Research and Future Perspectives - Bai, Qiyu; Dan, Qi; Mu, Zhe; Yang, Maokun (Frontiers in Psychology, 2019)
A growing body of research explores emoji, which are visual symbols in computer mediated communication (CMC). In the 20 years since the first set of emoji was released, research on it has been on the increase, albeit in a variety of directions. We reviewed the extant body of research on emoji and noted the development, usage, function and application of emoji. In this review article, we provide a systematic review of the extant body of work on emoji, reviewing how they have developed, how they are used differently, what functions they have and what research has been conducted on them in different domains. Furthermore, we summarize directions for future research on this topic.